Parametric modelling and the tessellation of architectural surfaces - Pitts, G.; Datta, Sambit (ANZAScA, 2008)
Parametric modelling is gaining in popularity as both a fabrication and design tool, but its application in the architectural design industry has not been widely explored. This form of modelling has the ability to generate complex forms with intuitively reactive components, allowing designers to express and to address the increasing need for seamless and bi-directional connectivity between the design, modelling and fabrication ambit. Despite its benefits, the process of parametric modelling can be lengthy and complex, without the level of intuitive programming required to make it a viable technique for use in architectural design. The ability to design small repeatable components and apply them to a larger governing surface geometry is one area of parametric modelling that has great design potential. This two level modelling control, of component and overall surface, can allow designers to explore new types of form generation subject parametric constraints. This process, coupled with Rapid Manufacturing (RM) and Computer Numerically Controlled (CNC) machines has the potential to significantly reduce the interface between design and fabrication.